Karakterisasi Morfologi Populasi Etlingera elatior (Jack) R.M.Sm. (Zingiberaceae) di Sumatera Barat - Zola Anjelia Putri; Nurainas Nurainas; Syamsuardi Syamsuardi (Universitas Andalas, 2017)
Research about morphological characterization of Etlingera elatior (Jack) R.M.Sm. (Zingiberaceae) was conducted from August to December 2016 in West Sumatra regions (Kepulauan Mentawai, Solok, and Padang Pariaman) and Padang city. Etlingera elatior has been used as traditional medicines for several diseases. Etlingera elatior was used for the treatment of various diseases. Effectivityof this plant depend on the preciseus in of the determinating variants type. The aim of this research was analyzed morphological variation among populations of Etlingera elatior. Survey and direct sampling method were used and continued by measurement of morphological characters of Etlingera elatior. Classification analyzed by cluster analysis with PAST program. Based on differentiation of the bract color of flowers, four variants of Etlingera elatior in West Sumatra were clarified those were 'red', 'pink', 'pale pink', and 'white' variant. The result of cluster analysis of 53 individuals Etlingera elatior indicated that many of 'white' and the 'red' variant were clustered in the same main cluster and individuals of 'pale pink' variant mostly clustered to 'red' variant and some of them were existed in the 'pink’ variant.